2017
DOI: 10.1371/journal.pone.0179315
|View full text |Cite
|
Sign up to set email alerts
|

Modelling community-control strategies to protect hospital resources during an influenza pandemic in Ottawa, Canada

Abstract: BackgroundA novel influenza virus has emerged to produce a global pandemic four times in the past one hundred years, resulting in millions of infections, hospitalizations and deaths. There is substantial uncertainty about when, where and how the next influenza pandemic will occur.MethodsWe developed a novel mathematical model to chart the evolution of an influenza pandemic. We estimate the likely burden of future influenza pandemics through health and economic endpoints. An important component of this is the a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
3
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(19 citation statements)
references
References 86 publications
0
19
0
Order By: Relevance
“…Similarly, in a study that included 762 H1N1 cases from both Australia and New Zealand, the mean cost per ICU patient was 61 368 € 2017 , with a per-day cost of 4767 € 2017 . 20 On the contrary, the non-ICU patient had a mean cost of 10 755 € 2017 ; however, overall Cost-effectiveness studies of measures in averting and/or responding to infectious respiratory disease outbreaks We identified 11 studies [23][24][25][26][27][28][29][30][31][32][33] referring to preparedness, preventative and response measures, to influenza outbreaks, presented in detail in online supplemental appendix 6. Two studies were observational (based in the Netherlands and the UK), 23 24 and the remaining nine were simulation models (four US models, with one study each modelled for Canada, France, Australia, Israel and one referring to developed countries in general).…”
Section: Comparative Cost Analysis Of Infectious Respiratory Disease Outbreaksmentioning
confidence: 99%
“…Similarly, in a study that included 762 H1N1 cases from both Australia and New Zealand, the mean cost per ICU patient was 61 368 € 2017 , with a per-day cost of 4767 € 2017 . 20 On the contrary, the non-ICU patient had a mean cost of 10 755 € 2017 ; however, overall Cost-effectiveness studies of measures in averting and/or responding to infectious respiratory disease outbreaks We identified 11 studies [23][24][25][26][27][28][29][30][31][32][33] referring to preparedness, preventative and response measures, to influenza outbreaks, presented in detail in online supplemental appendix 6. Two studies were observational (based in the Netherlands and the UK), 23 24 and the remaining nine were simulation models (four US models, with one study each modelled for Canada, France, Australia, Israel and one referring to developed countries in general).…”
Section: Comparative Cost Analysis Of Infectious Respiratory Disease Outbreaksmentioning
confidence: 99%
“…196 An influenza simulation tested seven interventions (e.g., social distancing); the authors concluded that with implementing all seven, the illness attack rate would be around 8 percent and with no intervention it would be 54 percent. 163 The COVID-19 studies are described in the subgroup analysis, and all other included studies are shown in Appendix C.…”
Section: Combined Medical and Nonpharmaceutical Countermeasures (Fourmentioning
confidence: 99%
“…Individuals placed in home quarantine have the same reductions but with only 50% compliance. 31,32 These estimates are summarized in Table 2. Since a lockdown is already in place, we did not analyze the individual effect of school and workplace closures.…”
Section: Interventionsmentioning
confidence: 99%